Obtenção de massa de mandioca com adição de maltodextrina de amido de milho waxy - Moro, Adriana Lima [UNESP]; Cabello, Claudio [UNESP] (EIA Energy in Agriculture, 2010)
This study aimed to the development of cassava mashed with added maltodextrin of waxy maize starch as an alternative to the semi-ready product. The experimental design was completely randomized using blocks in 4x7 factorial, with three replications. The treatments were the combination of maltodextrin concentrations added in the cassava mass (0, 5, 10 and 15% on dry weight) with storage time (0, 2, 4, 6, 8, 10 and 12 days after preparation) and two condition (environment and refrigerated temperature). The variety chosen to the processing was the IAC 576-70. The data were subjected to variance analysis. The means were compared by Tukey test at 5%. The content of maltodextrin from waxy maize starch to 15% was effective in controlling the increase of texture. The mass of cassava with the addition of maltodextrin showed to be product of easy preparation, showin IAC 576-70g viability to be produced in industrial scale.

Este trabalho teve como objetivo o desenvolvimento de massa alimentícia a base de mandioca com adição de maltodextrina de amido de milho waxy, como alternativa ao mercado de semi-prontos. O delineamento experimental foi em blocos inteiramente casualizados, em esquema fatorial 4x7, com três repetições. Os tratamentos foram constituídos pela combinação de concentrações de maltodextrina adicionadas à massa de mandioca (0, 5, 10 e 15% sobre peso seco), com o tempo de armazenamento (0, 2, 4, 6, 8, 10 e 12 dias após o preparo), e em duas condições de estocagem (temperatura ambiente e refrigerado). A variedade escolhida para o processamento foi a IAC 576-70. Os dados foram submetidos a análise de variância. As médias foram comparadas pelo teste de Tukey a 5%. O teor de maltodextrina de amido de milho waxy a 15% mostrou-se eficaz ao controle do aumento da textura. A massa alimentícia de mandioca com adição de maltodextrina (waxy) é um produto de fácil elaboração, apresentando viabilidade para ser produzida em escala industrial.
Obtention mashed of cassava (manihot esculenta c.) with addition of maltodextrin of starch of corn waxy
Keywords: Semi-ready; IAC 576-70; Texture; Semi-pronto; IAC 576-70; Textura